Monopolistic competition with pro- and countercyclical pricing - Helmut Zink (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1991)
We develop a market model which explains how prices react to short-run demand variations when the number of active price-setting firms is held fixed on its long-run level. We assume that for each firm the average production cost function is U-shaped, that customers are imperfectly informed about the quality of offers, and that customers may search for better offers. For low degrees of market transparency the long-run market outcome exhibits price dispersion with an endogenous finite number of firms. In this case, in the short-run, price mark-ups respond countercyclically to demand variations and productivity is procyclical. In the complementary case of higher degrees of market transparency, in the long-run we have a single-price equilibrium. In that case, in the short-run price mark-ups fall with decreasing demand while productivity diminishes with any deviation of demand from its long-run level.
Keywords: D40; D83; L11; 330; increasing returns; monopolistic competition; business cycle theory